2018
DOI: 10.1002/jcp.27865
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in TMEM16A: Structure, function, and disease

Abstract: TMEM16A (also known as anoctamin 1, ANO1) is the molecular basis of the calcium‐activated chloride channels, with ten transmembrane segments. Recently, atomic structures of the transmembrane domains of mouse TMEM16A (mTMEM16A) were determined by single‐particle electron cryomicroscopy. This gives us a solid ground to discuss the electrophysiological properties and functions of TMEM16A. TMEM16A is reported to be dually regulated by Ca2+ and voltage. In addition, the dysfunction of TMEM16A has been found to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 142 publications
(382 reference statements)
0
57
0
2
Order By: Relevance
“…One of the most intriguing features of the TMEM16 family proteins is that it's members can transport ions and/or phospholipid, two seemingly distinct classes of substrates, despite highly conserved structures. 3,7 Our previous study of TMEM16F lipid scramblase has suggested a conserved "clam-shell" model of activation for the TMEM16 family proteins. 17 Whether a TMEM16 protein has channel and/or scramblase activities is likely determined by how wide the same pore may be dilated (e.g., see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most intriguing features of the TMEM16 family proteins is that it's members can transport ions and/or phospholipid, two seemingly distinct classes of substrates, despite highly conserved structures. 3,7 Our previous study of TMEM16F lipid scramblase has suggested a conserved "clam-shell" model of activation for the TMEM16 family proteins. 17 Whether a TMEM16 protein has channel and/or scramblase activities is likely determined by how wide the same pore may be dilated (e.g., see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ -activated Clchannels (CaCCs) direct the flow of information from calcium signaling to Cl − current and are involved in numerous physiological functions including neuronal excitation, smooth muscle contraction and airway fluid secretion. 1,2,3 After two decades of searching, the molecular identity of CaCC was finally determined as TMEM16A. 2,4,5,6 TMEM16A, also known as anoctamin-1 (ANO1), belongs to the TMEM16 family of multi-functional proteins that include both CaCC and Ca 2+ -activated lipid scramblase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study using several epithelial tumor cell lines, it was discovered that DOG1 degradation was crucial for its antitumoral effects (29). Since then, advancements have been made in the knowledge of CaCC inhibitors possessing not only inhibitory activities but also DOG1 protein degradation properties, reviewed in detail elsewhere (30). Therefore, we sought to evaluate if enhanced DOG1 inhibition would lead to functional antitumoral effects in well-established GIST tumor cell lines.…”
mentioning
confidence: 99%